Metastatic colorectal cancer and type 2 diabetes: prognostic and genetic interactions. Issue 2 (19th November 2021) - Ottaiano, Alessandro; Circelli, Luisa; Santorsola, Mariachiara; Savarese, Giovanni; Fontanella, Daniela; Gigantino, Valerio; Di Mauro, Annabella; Capuozzo, Maurizio; Zappavigna, Silvia; Lombardi, Angela; Perri, Francesco; Cascella, Marco; et al.
Abstract : The present study was undertaken to analyze prognostic and genetic interactions between type 2 diabetes and metastatic colorectal cancer. Patients' survival was depicted through the Kaplan–Meier product limit method. Prognostic factors were examined through the Cox proportional‐hazards regression model, and associations between diabetes and clinical‐pathologic variables were evaluated by the χ 2 test. In total, 203 metastatic colorectal cancer patients were enrolled. Lymph nodes ( P = 0.0004) and distant organs (> 2 distant sites, P = 0.0451) were more frequently involved in diabetic patients compared with those without diabetes. Diabetes had an independent statistically significant negative prognostic value for survival. Highly selected patients with cancer and/or diabetes as their only illness(es) were divided into three groups: (a) seven oligo‐metastatic patients without diabetes, (b) 10 poly‐metastatic patients without diabetes, and (c) 12 poly‐metastatic diabetic patients. These groups of patients were genetically characterized through the Illumina NovaSeq 6000 (San Diego, CA, USA) platform and TruSigt™Oncology 500 kit, focusing on genes involved in diabetes and colorectal cancer. Gene variants associated with diabetes and cancer were more frequent in patients in group 3. We found that type 2 diabetes is a negative prognostic factor for survival in colorectal cancer. Diabetes‐associated gene variants could concur with malignancy, providing a rational basis for innovative models of tumor progression and therapy. Abstract : Type 2 diabetes (T2D) is a frequent comorbidity among metastatic colorectal cancer patients. Here we show that T2D is a negative prognostic factor and hypothesize that genetic polymorphisms involved in diabetes could concur with malignancy providing new insights for innovative models of tumor progression and therapy in this subset of patients.